2023
DOI: 10.3847/1538-3881/acb34b
|View full text |Cite
|
Sign up to set email alerts
|

Systematic KMTNet Planetary Anomaly Search. VII. Complete Sample of q < 10−4 Planets from the First 4 yr Survey

Abstract: We present the analysis of seven microlensing planetary events with planet/host mass ratios q < 10−4: KMT-2017-BLG-1194, KMT-2017-BLG-0428, KMT-2019-BLG-1806, KMT-2017-BLG-1003, KMT-2019-BLG-1367, OGLE-2017-BLG-1806, and KMT-2016-BLG-1105. They were identified by applying the Korea Microlensing Telescope Network (KMTNet) AnomalyFinder algorithm to 2016–2019 KMTNet events. A Bayesian analysis indicates that all the lens systems consist of a cold super-Earth orbiting an M or K dwarf. Together with 17 previous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 84 publications
0
18
1
Order By: Relevance
“…However, in contrast to the majority of published by-eye discoveries (but similar to most of the new AnomalyFinder discoveries reported in Zang et al 2021Zang et al , 2022Zang et al , 2023Gould et al 2022;Hwang et al 2022;Jung et al 2022), most of the planetary events reported in this paper have only upper limits on ρ, and these limits are mostly not very constraining. As discussed by Gould et al (2022), in these cases, θ ast determinations are not likely to be of much use, either now or in the future.…”
Section: Source Propertiescontrasting
confidence: 50%
See 2 more Smart Citations
“…However, in contrast to the majority of published by-eye discoveries (but similar to most of the new AnomalyFinder discoveries reported in Zang et al 2021Zang et al , 2022Zang et al , 2023Gould et al 2022;Hwang et al 2022;Jung et al 2022), most of the planetary events reported in this paper have only upper limits on ρ, and these limits are mostly not very constraining. As discussed by Gould et al (2022), in these cases, θ ast determinations are not likely to be of much use, either now or in the future.…”
Section: Source Propertiescontrasting
confidence: 50%
“…Among these five planets, none is truly exceptional in its own right, although OGLE-2019-BLG-0679 has a relatively large normalized projected separation, s = 2.18. Indeed, among the 53 previously published (or summarized) AnomalyFinder planets from 2018 and 2019 (Gould et al 2022;Jung et al 2022;Zang et al 2022Zang et al , 2023, only one had a larger separation, i.e., OGLE-2018-BLG-0383, with s = 2.45 (Wang et al 2022).…”
Section: Summary Of All 2019 Subprime Anomalyfinder Planetsmentioning
confidence: 98%
See 1 more Smart Citation
“…The fourth criterion is that the maximum value of the source brightness must be >5 times larger than the flux error at the time. We note that this criterion is more conservative than the criterion that is used in the analysis by KMTNet (Zang et al 2022(Zang et al , 2023. The fifth criterion is that there are at least three consecutive points with the observed flux deviating from the constant baseline by more than 5σ.…”
Section: Flux Determinationmentioning
confidence: 99%
“…We have already done the systematic searches for the 2018 prime field (Wang et al 2022;Hwang et al 2022;Gould et al 2022), 2018 sub-prime fields (Jung et al 2022), 2019 prime fields (Zang et al 2021;Hwang et al 2022;Zang et al 2022a), and 2019 sub-prime fields (Jung et al 2023). In addition, Zang et al (2023) present a complete sample of planets with the mass ratio q < 10 −4 discovered from all candidate events observed from 2016 to 2019. This is the 9th work to build the complete sample, which is conducted for the 2016 prime-fields (i.e., BLG01, BLG41, BLG02, BLG42, BLG03, BLG43).…”
Section: Introductionmentioning
confidence: 99%